SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF FAMILY CONFLICTS IN YOUNG FAMILIES: https://doi.org/10.5281/zenodo.15407917 - Ergasheva, Mokhina (Journal of Contemporary World Studies, 2025)
This article analyzes the causes of conflicts that occur in young families, the dynamics of rejection and socio-psychological factors in their management. The study aims to identify the link between family environment, interpersonal communication, social support, and conflict resolution strategies. The results of the study showed that conflict in young families is often caused by Communication Disorders, role conflicts, and emotional deficits. The article also presents practical proposals aimed at reducing these conflicts.